Producción científica y licenciamiento de escuelas de medicina en el Perú - Mayta Tristán, Percy (2019)
The new university law 30220 of 2014 introduced the mandatory institutional licensing of all Peruvian universities by the National Superintendence of Higher University Education (SUNEDU, in Spanish). The first undergraduate program to go through this process will be medicine. The licensing of medical programs is necessary to ensure that the conditions in which the program is taught in Peru are adequate, with a high probability of closing some medical schools. Once a medical school has demonstrated that it meets the basic conditions of quality, a qualitative and quantitative evaluation is carried out that includes three criteria: scientific production in the Web of Science, impact measured through the H index, and results of the national medical exam, to determine the years of licensing. This article evaluates the quantitative indicators linked to research using Web of Science and Scopus, in addition to making technical and methodological revisions of them. Suggestions for the other indicators are also covered by this article.